Global Potential and Trade‐Offs of Conservation Tillage for Crop Productivity and Ecosystem Services - Wanyang Zhang; Linchuan Fang; Wenju Zhang; Chaoqun Wang; Tianyi Qiu; Xiaokun Li; Min Huang; Bolin Li; Ling Xia; Lai Peng; Yifeng Xu; Xiaoyong Wu; et al. (Global Change Biology, 2026)
Conservation Agriculture (CA) is pivotal to achieve sustainable intensification, yet the global efficacy of its core practice, conservation tillage (CT), remains debated regarding the trade‐offs between crop productivity and ecosystem services across diverse environmental contexts. Here, we conducted a second‐order meta‐analysis, synthesizing 69 published meta‐analyses, to elucidate the context‐dependent drivers regulating the “win‐win” outcomes of CT. Globally, CT reduced greenhouse gas (GHG) emissions by 5%, increased soil organic carbon sequestration by 21%, increased soil fertility by 11%, and reduced soil erosion by 12%, all while maintaining crop yields comparable to conventional tillage. However, CT can also emerge as a partial trade‐off between crop yields and ecosystem services, notably between crop yield and GHG mitigation. These trade‐offs were strongly regulated by climatic and edaphic conditions as well as management intensity. For instance, strong synergies between crop productivity and multiple ecosystem services were more pronounced in (semi‐)arid regions characterized by low temperatures and low precipitation, as well as in coarse‐textured alkaline soils. Furthermore, integrating CT with residue retention and crop rotations maximized these synergies, mitigating potential yield penalties. Collectively, our synthesis demonstrates that context‐specific refinement of CT implementation is essential to reconcile agricultural productivity with ecosystem services, thereby advancing climate‐resilient agricultural systems globally.